E-113 Middle meningeal artery embolization for treatment of chronic subdural hematoma: A prospective institutional case series. (4th August 2020) - Rinaldo, L; Cloft, H; Brinjikji, W
Abstract : Background: Embolization of the middle meningeal artery (MMA) has emerged a potential treatment for chronic subdural hematoma (cSDH), either as a stand-alone therapy or an adjunct to surgical evacuation. Methods: Information on patients with a cSDH at least 10 mm in maximal thickness selected for MMA embolization was entered into a prospectively collected database. The embolization procedure consisted of MMA catheterization followed by injection of 150–250 µm polyvinyl alcohol (PVA) particles until occlusion of the MMA distal to the sphenoid ridge. For patients who also underwent surgical evacuation, MMA embolization was performed after surgery in all cases. Descriptive statistics of treatment outcomes, which included cSDH size on final head CT and the incidence of cSDH surgical evacuation after MMA embolization, are provided. Results: MMA embolization was performed in 23 patients with 29 cSDHs. The mean age of the cohort was 72.3 years [Standard deviation (SD) = 9.2] and a majority of patients were male (n=24, 82.8%). History of anti-coagulation use was present in 14 patients (60.9%). Mean maximal dimension and associated midline shift of treated cSDHs were 18.1 (SD=4.9) and 4.6 mm (SD=3.9). Surgical evacuation prior to MMA embolization was performed for 12 cases (41.4%). A thromboembolic complication during MMA embolization resulting in a new minor neurologic deficit occurred in a single patient (4.3%). Overall, 27 cSDHs (93.1%) were reduced in size on final follow-up CT, and 10 were completely resolved (34.4%). Stratified by initial medical versus surgical management, 88.2% (n=15/17) and 100.0% (n=12/12) of cSDHs were reduced in size and 33.3% (n=4/12) and 35.3% (n=6/17) were completely resolved on last follow-up CT. Two cSDHs (6.9%) in a single patient initially treated with surgery required repeat surgical evacuation after MMA embolization. Mean time between MMA embolization and last follow-up head CT was 3.7 months (SD=3.1). Conclusion: Our preliminary results suggest MMA embolization may be an effective treatment for cSDHs. Randomized trials are indicated. Disclosures: L. Rinaldo: None. H. Cloft: None. W. Brinjikji: None.